Structural Equation Modeling of Marital Adjustment with Early Maladaptive Schemas Considering the Mediating Role of Marriage Styles in Men - Kabiri Afshar, Tahereh; Zargham Hajebi, Majid; Abdi Zarin, Sohrab (Applied Family Therapy Journal (AFTJ), 2024)
Objective: The present study aimed to model the structural equations of marital adjustment with early maladaptive schemas considering the mediating role of marriage styles in men.Methods: The research method was descriptive-correlational. The statistical population included married men from the general population in districts 2, 7, and 11 of Tehran in the first quarter of 2022. A total of 300 men were selected as the research sample using purposive sampling. Data were collected using the Marital Adjustment Questionnaire (Busby et al., 1995), Young Schema Questionnaire (Young, 1994), and a researcher-made Marriage Styles Questionnaire. Data analysis was conducted using Pearson's correlation coefficient and structural equation modeling with SPSS-24 and AMOS-24 software.Findings: The results indicated a good fit for the model linking marital adjustment with early maladaptive schemas and marriage styles. The final model fit indices showed a negative and significant relationship between early maladaptive schemas and marital adjustment. Additionally, marriage styles mediated the relationship between early maladaptive schemas and marital adjustment.Conclusion: Based on the findings, it can be concluded that since marriage is one of the significant life decisions, focusing on early maladaptive schemas and pre-marital education can enhance marital adjustment, improve marriage styles, and sustain relationships, thereby increasing the marital quality of life.